Negotiating the New Moon: Social Media and the Dynamics of Hijri Calendar Determination among Muslims - Fauzi, Ahmad (Fakultas Syari'ah dan Hukum UIN Walisongo, 2025)
Social media has become a primary platform for Muslims to access religious information, including the determination of the Hijri month, which is central to worship such as Ramadan fasting, Eid al-Fitr, and Eid al-Adha. This study explores how social media shapes understandings and debates regarding the ḥisāb and rukyat methods for marking the start of the Hijri month. Using a netnographic approach, data were collected from various platforms and analyzed through content analysis to identify dominant narratives, information patterns, and forms of debate in the digital sphere. Findings reveal three modes of understanding: academic-scientific (based on astronomical data and ḥisāb), normative-textual (rooted in classical arguments and religious authority), and popular (driven by public opinion, humor, and satire). Debates are fragmented into scientific-argumentative, emotional-narrative, and humorous-satirical forms, shaped by authoritative, semi-authoritative, and lay actors. The study concludes that social media plays a dual role: enhancing digital literacy in Islamic astronomy while simultaneously intensifying discourse polarization, highlighting the need for inclusive religious communication strategies.